Nghiên cứu chế tạo vật liệu compozit trên cơ sở EVA và tro bay ở trạng thái nóng chảy - Hoàng, Thái; Đức, Vũ Minh; Giang, Nguyễn Vũ; Thẩm, Đỗ Quang; Trọng, Vũ Minh (Vietnam Journal of Chemistry, 2014)
The copolymer composites of ethylene-vinyl acetate/fly ash (EVA/FA) with different content of FA were prepared by melt mixing in a Haake Rheomixer. The relative melt viscosity of the composites increased with increasing the FA conten added into EVA. The mechanical properties of the composites are lower than those of EVA and decreased with increasing FA content. When the fly ash treated with silane, the relative melt viscosity of the EVA/treated FA composites is lower the EVA/untreated FA composites. The tensile strength and the elongation at break of the EVA/treated FA composites is higher the EVA/untreated FA composites. The comparison of the properties of composites filled with treated and untreated fly ash revealed that the composites with treated fly ash showed better reinforcing properties.